A mission with a clear vision: eliminating the problems of public policy in the Malaysian Contracts Act 1950 - Kho, Feng Ming; Asma Hakimah Ab Halim; Sakina Shaik Ahmad Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2018)
Public policy in the Malaysian Contracts Act 1950 have caused much debate among the judges in Malaysia. The underlying problem is due to the fact that the provision in the Act itself has failed to lay down a proper legal framework as to what agreements are against public policy. As a short term solution to curb these uncertainties in the law, the judges in Malaysia have adopted different trends in adjudication and this in turn contributed to inconsistencies in the law, a phenomena not commonly practiced in the common law system. This article seeks to propound that Malaysia should establish a proper legal framework to regulate contracts which are against public policy. As Malaysia is advancing towards as a holistic hub in Islamic banking and finance, perhaps adopting the maqasid al-shari’ah as a framework of regulation can be a useful starting point, bearing in mind that transposing case laws from other jurisdictions may not be the long term solution.